Determine the quadratic ax^2+bx+c, if a,b,c are terms of arithmetic sequence. a=2t-3,b=5t+1,c=4t-7
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We are given that in the quadratic equation ax^2+bx+c, a,b,c are terms of arithmetic sequence such that a = 2t-3, b = 5t+1 and c = 4t-7
As consecutive terms of an AP have a common difference:
4t - 7 - 5t - 1 = 5t + 1 - 2t + 3
=> -t - 8 = 3t + 4
=> 4t = -12
=> t = -3
a = 2t - 3 = -6 - 3 = -9
b = 5t + 1 = -15 + 1 = -14
c = 4t - 7 = -12 - 7 = -19
The quadratic equation is -9x^2 - 14x - 19 = 0
=> 9x^2 + 14x + 19 = 0
The required quadratic equation is 9x^2 + 14x + 19 = 0
Related Questions
- need to calculate sum of 3 consecutive terms of arithmetic sequence x+4,3x,13x-2
- 1 Educator Answer
- What is the first term of arithmetic sequence if the sum a1+a2+...a13=130? a4,a10,a7 are also...
- 1 Educator Answer
- Find the first term and the common difference of the arithmetic sequence if a2-a6+a4=-7 and...
- 1 Educator Answer
If 2t-3, 5t+1, 4t-7, are the consecutive terms of an arithmetical progression, then the middle term is the arithmetical mean of its neighbor terms.
5t+1=(2t-3+4t-7)/2
We'll combine like terms inside brackets:
5t+1=(6t-10)/2
5t+1=2(3t-5)/2
5t+1=3t-5
We'll move the terms in t to the left side and the numbers alone to the right side:
5t-3t=-1-5
2t=-6
t=-6/2
t=-3
Since the coefficients a,b,c are depending on t, we'll determine them:
a = 2t - 3
a = -6 - 3
a = -9
b = 5t + 1
b = -15+1
b = -14
c = 4t - 7
c = -12 - 7
c = -19
The quadratic equation is: -9x^2 - 14x - 19 = 0
We'll multiply by -1 and we'll get:
9x^2 + 14x + 19 = 0
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Student Answers